Differences in ventricular wall composition may explain inter-patient variability in the ECG response to variations in serum potassium and calcium - Bukhari, Hassaan A.; Sánchez, Carlos; Laguna, Pablo; Potse, Mark; Pueyo, Esther (Frontiers in Physiology, 2023)
Objective: Chronic kidney disease patients have a decreased ability to maintain normal electrolyte concentrations in their blood, which increases the risk for ventricular arrhythmias and sudden cardiac death. Non-invasive monitoring of serum potassium and calcium concentration, [K + ] and [Ca 2+ ], can help to prevent arrhythmias in these patients. Electrocardiogram (ECG) markers that significantly correlate with [K + ] and [Ca 2+ ] have been proposed, but these relations are highly variable between patients. We hypothesized that inter-individual differences in cell type distribution across the ventricular wall can help to explain this variability.Methods: A population of human heart-torso models were built with different proportions of endocardial, midmyocardial and epicardial cells. Propagation of ventricular electrical activity was described by a reaction-diffusion model, with modified Ten Tusscher-Panfilov dynamics. [K + ] and [Ca 2+ ] were varied individually and in combination. Twelve-lead ECGs were simulated and the width, amplitude and morphological variability of T waves and QRS complexes were quantified.Results: Both simulations and patients data showed that most of the analyzed T wave and QRS complex markers correlated strongly with [K + ] (absolute median Pearson correlation coefficients, r, ranging from 0.68 to 0.98) and [Ca 2+ ] (ranging from 0.70 to 0.98). The same sign and similar magnitude of median r was observed in the simulations and the patients. Different cell type distributions in the ventricular wall led to variability in ECG markers that was accentuated at high [K + ] and low [Ca 2+ ], in agreement with the larger variability between patients measured at the onset of HD. The simulated ECG variability explained part of the measured inter-patient variability.